Comparison Between Videographic and Photographic Methods in Assessing Coral Reef Bethnic Communities - Cabaitan, Patrick; Licuanan, Wilfredo; Gomez, Edgardo (Science Diliman: A Journal of Pure and Applied Sciences; Vol 19 No 1 (2007), 2007)
Continuous degradation of coral reefs creates a need for techniques that can assess reefs condition rapidly and efficiently. The Video transect survey is commonly used to monitor benthic communities because it is rapid, provides a permanent historical record of the data, and can help minimize observer bias. But this technology is not readily available to most research institutions because of its high cost. In this study, a low cost photographic method was used to survey benthic communities in the subtidal flat inside Caniogan Marine Sanctuary, Tondol, Anda, Pangasinan. Results from this method were then compared with those from videographic methods. For the low cost photographic method, ten regularly spaced shots were directly taken from each 5m transect, totaling to 100 frames. Ten 5m x ~0.25m video transects were also run over each of the twenty selected patch reefs, covering the whole demarcated area. Ten regularly spaced frames were then taken from the videotape in each transect, totaling to 100 frames in each patch reef. In the laboratory, all frames were analyzed using the systematic 5-point method. Both methods yielded comparable time in field data collection. However, videographic method demanded more time in post-collection computer analysis and it is more costly due to the required additional computer software and hardware. Pairwise T-tests and Analysis of similarities (ANOSIM) revealed that both methods gathered similar results in terms of the diversity (P>0.05) and in terms of percentage composition (P>0.05) of life forms recorded, suggesting that both can be used interchangeably in benthic community surveys.